O patrimônio quilombola de Tururu-Ce. - Alves, Eduardo Rodrigues (2018)
Through a qualitative analysis of cultural and social clipping, the work seeks to understand the process of patrimonial recognition of the quilombolas territories of the municipality of Tururu-CE from relations and problematics that challenge their visibility in the municipal scope. The Quilombo Remnant Communities (CRQs) of Tururu, Conceição dos Caetanos and Água Preta, present challenges regarding their recognition as geoeducational patrimony. The conceptual basis of the study was directed towards the understanding of territoriality and the cultural aspects of these groups. The methodology included documental research, fieldwork with semi-structured interviews and practices of Patrimonial Education and Participatory Mapping. Intra-community, intercommunal and intermunicipal relations have been identified, which reflect challenges and demand strategies for the recognition of these CRQs. Based on geoeducational practices, it was possible to understand that the value recognition of these territories is based on the capacity of the communities themselves to claim, but also on the capacity of public authorities to assist in their different spheres. Therefore, it is demanded a greater articulation between different agents in different scales, as well as the improvement of geoeducational practices to foment this value process.